2018
DOI: 10.1021/acs.accounts.8b00102
|View full text |Cite
|
Sign up to set email alerts
|

Optothermal Manipulations of Colloidal Particles and Living Cells

Abstract: Optical manipulation techniques are important in many fields. For instance, they enable bottom-up assembly of nanomaterials and high-resolution and in situ analysis of biological cells and molecules, providing opportunities for discovery of new materials, medical diagnostics, and nanomedicines. Traditional optical tweezers have their applications limited due to the use of rigorous optics and high optical power. New strategies have been established for low-power optical manipulation techniques. Optothermal mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 56 publications
1
87
0
3
Order By: Relevance
“…As far as we know, this is the first all-optical technique for dynamic nanomanipulation in the bulk. Various alternate approaches have relied on combining plasmonic tweezers with additional forcing schemes, such as direct mechanical manipulation of tethered nano-patterned optical fibers 50 , integration with magnetic nanorobots 51 , electro-kinetic flows 14,52 , thermal forces in conjunction with specific chemical moieties 2931,53 , etc. The ACTs discussed here could be operated remotely to trap and maneuver subwavelength colloidal cargo, using lower optical power than conventional gaussian beam tweezers 5,54 .…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this is the first all-optical technique for dynamic nanomanipulation in the bulk. Various alternate approaches have relied on combining plasmonic tweezers with additional forcing schemes, such as direct mechanical manipulation of tethered nano-patterned optical fibers 50 , integration with magnetic nanorobots 51 , electro-kinetic flows 14,52 , thermal forces in conjunction with specific chemical moieties 2931,53 , etc. The ACTs discussed here could be operated remotely to trap and maneuver subwavelength colloidal cargo, using lower optical power than conventional gaussian beam tweezers 5,54 .…”
Section: Discussionmentioning
confidence: 99%
“…13 This photothermal effect drives the thermophoresis as repulsive force, which sweeps the nanoparticles out of trap from hot to cold. [14][15][16][17] By adjusting the ratios of the attractive-and the repulsive forces acting on the nanocolloids, the following three modes on optical manipulation will be available: i) optical trapping mode entirely governed by the gradient force, ii) thermophoretic depletion mode dominated by the thermophoresis, and iii) selective trapping and separation mode based on the interplay of both contributions.…”
Section: Textmentioning
confidence: 99%
“…In addition to the optical force and photothermal effect, the electric fields can also contribute to the trapping and manipulation [101][102][103][104]. Kotnala et al demonstrated an opto-thermophoretic fiber tweezer (OTFT) [105], which combined the photothermal effect and electric field effect into the fiber tweezers.…”
Section: Opto-thermophoretic Fiber Tweezersmentioning
confidence: 99%